MicroRNAs in regulatory T cells. (1st June 2018) - Phiwpan, Krung; Zhou, Xuyu
Highlights: Regulatory T (Treg) cells is a highly dynamic population. Treg cell-specific microRNA ablation results in fatal autoimmune disease. MicroRNAs play critical role in regulating heterogeneity and plasticity of Tregs.